SOLVING DIAGONAL SUDOKU PUZZLE 9X9 GRID BY JAVA PROGRAMMING ALGORITHM - Nur Intan Syafinaz Ahmad; Nurhuda Ismail; Ahmad Khudzairi Khalid; Muhammad Syawal Abd Halim (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2019)
Sudoku is one of the well known puzzle game that have been played world wide. There are many types of Sudoku puzzle that exist to be played such as diagonal, diagonal even, diagonal odd, isosudoku, lucky seven, parquet and others. This paper focus on solving the diagonal Sudoku by using Java Programming Algorithm for 9x9 grid. For normal Sudoku, the number 1-9 must be filled up in all grids with no number duplication conflict in the row, column and 3x3 grid inside the Sudoku puzzle itself. While the diagonal Sudoku has one extra condition to be considered that is the number 1-9 must also be filled in the diagonal place which start from the most upper-left or bottom-left to the most upper-right or bottomright of the puzzle. There is no conflict with other grid in its diagonal region. In order to solve the puzzle, we have to contruct algorithm and translate it using Java Programming Language. The guessing method with backtrack approach has been selected to construct the algorithm. This Java Programming are designed to solve the diagonal Sudoku puzzle for 9x9 grid.